2018
DOI: 10.1016/j.cub.2018.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Population Turnover in Remote Oceania Shortly after Initial Settlement

Abstract: Ancient DNA from Vanuatu and Tonga dating to about 2,900-2,600 years ago (before present, BP) has revealed that the "First Remote Oceanians" associated with the Lapita archaeological culture were directly descended from the population that, beginning around 5000 BP, spread Austronesian languages from Taiwan to the Philippines, western Melanesia, and eventually Remote Oceania. Thus, ancestors of the First Remote Oceanians must have passed by the Papuan-ancestry populations they encountered in New Guinea, the Bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 41 publications
1
50
0
1
Order By: Relevance
“…The development of DNA library construction methods that exploit molecular features of aDNA, in particular the presence of damage in the form of single-strand breaks [86] and/or deaminated cytosines [87], has also enhanced our ability to access aDNA templates. Finally, target enrichment approaches, aimed at the characterization of organellar DNA [88] or of a limited number of mitochondrial and nuclear loci [89], or up to hundreds of millions of SNPs scattered throughout the nuclear genome [90] and even of the entire nuclear genome [91, 92], now contribute to the retrieval of the genome-scale information required to address major biological questions in both a cost- and time-effective manner. It is worth noting that a number of computational approaches have also helped to quantify DNA damage [93, 94], to reduce its impact on downstream analyses [94, 95], and to improve the sensitivity and accuracy of aDNA read alignments [96–99].…”
Section: Evolutionary Processes Inferred From Ancient Dna (Allochronimentioning
confidence: 99%
“…The development of DNA library construction methods that exploit molecular features of aDNA, in particular the presence of damage in the form of single-strand breaks [86] and/or deaminated cytosines [87], has also enhanced our ability to access aDNA templates. Finally, target enrichment approaches, aimed at the characterization of organellar DNA [88] or of a limited number of mitochondrial and nuclear loci [89], or up to hundreds of millions of SNPs scattered throughout the nuclear genome [90] and even of the entire nuclear genome [91, 92], now contribute to the retrieval of the genome-scale information required to address major biological questions in both a cost- and time-effective manner. It is worth noting that a number of computational approaches have also helped to quantify DNA damage [93, 94], to reduce its impact on downstream analyses [94, 95], and to improve the sensitivity and accuracy of aDNA read alignments [96–99].…”
Section: Evolutionary Processes Inferred From Ancient Dna (Allochronimentioning
confidence: 99%
“…Elements of this might be seen in the preliminary ancient genetics generated for some of the Vanuatu Lapita sites. At Teouma the analysis of the aDNA of four individuals indicates largely Asian heritage (Lipson et al 2018;Skoglund et al 2016), while at the slightly later site of Uripiv individuals shared a mixed Asian and Papuan heritage (Posth et al 2018). Morphological study of Vanuatu skeletal remains and other comparative samples reinforces the idea of population change in western Remote Oceania as occurring within the Lapita period (Valentin et al 2016).…”
Section: Discussionmentioning
confidence: 65%
“…There is still limited study of Vanuatu (Cox 2007) and New Caledonia (Kouneski 2009) and most consideration of genetic history in the region is dependent on small older samples with apparently limited genealogical data (Friedlaender et al 2007;Kayser 2010). Most recently, and after this paper was initially submitted, much more work has been published for Vanuatu, and most significantly on ancient DNA from the Pacific (Skoglund et al 2016;Lipson et al 2018;Posth et al 2018). Delfin et al (2012) have reported on the first comprehensive genetic study of the Solomon Islands, which has sampled mitochondrial DNA (mtDNA) and nonrecombining Y chromosomes (NRY) from over 700 individuals in 18 populations in the Solomons, from Choiseul in the west to Tikopia in the east, including 46 individuals from villages on the south-western and north-eastern coasts of Santa Cruz.…”
Section: Genetic Evidencementioning
confidence: 99%
“…In the Principal Components Analysis they provide as Figure 1b, the Lapita samples in fact plot tightly off by themselves and not in with the 'Polynesian' samples nor in with the 'East Asian' samples, although closest to those from the Northern Philippines-so they are unlike any modern samples. The recent papers by Posth et al (2018) and Lipson et al (2018) build on this result in a very commendable fashion by extracting ancient DNA from a large sample (19 and 14, respectively) of prehistoric human remains from across the Pacific and through time, and in addition collecting additional DNA from modern Ni-Vanuatu (27 and 185 samples respectively). Both papers conclude that the earliest Lapita individuals are unlike any modern populations in Near Oceania, including the Solomon Islands, while all the Post-Lapita individuals-including an individual dating to 2630-2350 cal.…”
Section: Terra Australis 52mentioning
confidence: 99%